The Pi-Theorem Applications to Fluid Mechanics and Heat and Mass Transfer - Yarin, L.P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This volume presents applications of the Pi-Theorem to fluid mechanics and heat and mass transfer. The Pi-theorem yields a physical motivation behind many flow processes and therefore it constitutes a valuable tool for the intelligent planning of experiments in fluids. After a short introduction to the underlying differential equations and their treatments, the author presents many novel approaches how to use the Pi-theorem to understand fluid mechanical issues. The book is a great value to the fluid mechanics community, as it cuts across many subdisciplines of experimental fluid mechanics.
Basics of the dimensional analysis -- Application of the Pi-theorem to establish self-similarity and reduce partial differential equations to the ordinary ones -- Drag force acting on a body moving in viscous fluid -- Laminar flows in channels and pipes -- Jet flows -- Heat and mass transfer -- Turbulence -- Combustion processes.
Keywords: Engineering; Computer science -- Mathematics; Hydraulic engineering; Engineering; Engineering Fluid Dynamics; Fluid- and Aerodynamics; Engineering Thermodynamics, Heat and Mass Transfer; Computational Mathematics and Numerical Analysis